Samins Arranged Marriage Rituals in Today Javaneses Society - Fransiska Rahayu Myrlinda (Journal of Language and Literature, 2019)
Arranged marriage means a marriage in which the parents have chosen and planned to whom their son or daughter would marry with. This form of marriage commonly has perception that it is held only for the needs of their parents without any consideration of their childrens feelings. It results in there is no freedom for either bride or groom to choose their own partner. All the things have been set according to the parents will. In arranged marriage, usually they even never have a chance to meet each other before the marriage occurs. On the other hand, arranged marriage does exist and has been believed as a culture for Samin people in Kelopodhuwur, Blora, Indonesia. It is held from generation to generation which makes it impossible for the children to deny. It is used by the people in Samin community to preserve their identity from extinction. There are lots of unique rituals should be done for Samin people in holding this arranged marriage. The identity theory was used to support the reliable data to the research.